The Local Role of Southern Tourism Plantations in Defining a Larger Southern Regional Identity as Reflected in Tourists' Surveys*. Issue 3 (2nd July 2020) - Bright, Candace Forbes; Carter, Perry L.; Modlin, E. Arnold; Hanna, Stephen P.; Potter, Amy E.; Alderman, Derek H.
ABSTRACT: To what extent does local variation exist in the expressed interests of planta- tion museum tourists? While the study of plantation museums is of growing importance in the tourism literature, these existing studies have tended to focus on a single site or a single region. This study examines data collected at several southern plantations across multiple smaller areas in the U.S. Southeast. Specifically, we are curious about tourists' interests in select topics, such as slavery and the role of women on the plantation, among others in three regions: River Road, Louisiana; Charleston, South Carolina; and James River, Virginia. We hypothesize that each region has absorbed different local identities and histories that constitute multiple Souths. Employing conditional inference trees on plantation museum tourist interest ratings and rankings, we find varying social representations by in these local communities, with interest in Enslaved playing an important role in the variation of these imaginings.